A HYPOTHETICAL COMBINATION METHOD TO PROVIDE DATA FOR FORMATION WATER COMPATIBILITY - Herlan Adim (Testing Center for Oil and Gas LEMIGAS, 1999)
Industrial Water Technology, information concerning formation water, is required primarily in water injection projects to define the possibility of injection well plugging.